How can scientists and designers find ways of working together? A case study of playful learning to co-design visual interpretations of immunology concepts. Issue 9 (2nd September 2022) - Macdonald, Iain; Malone, Eva; Firth, Richard
ABSTRACT: In UK HE institutions there is a growing realisation and appreciation for academic disciplines to seek research partners beyond their own subject (QAA. 2018. Enterprise and entrepreneurship education: Guidance for UK higher education providers. Accessed 1 April 2020. https://www.qaa.ac.uk/docs/qaas/enhancement-and-development/enterprise-and-entrpreneurship-education-2018.pdf?sfvrsn=15f1f981_8 ). The rewards for developing understanding and sharing methodologies can extend beyond solving research questions to enhance the researcher and student learning experience. When academic researchers and students are given the opportunity to work together outside the confines of the curriculum and inhabit a space of 'otherness' in playful learning, liberated thinking and uninhibited ideation can transform patterns of learning and problem solving. This study aimed to use interdisciplinary co-design workshops to create opportunities for bringing scientists and designers to work together, exposing them to the challenges of developing accessible immunology materials and to develop a pathway to reconcile them through empathy and reflective practice. Our research evidence showed that projects like this are inclusive and engaging. Student participants were excited and inspired by each other's different knowledge and skills, but were also rewarded by overcoming different cultures of learning and communication. The efficacy of playful learning's 'otherness', and the 'out-of-hours' aspect were also interrogated and reflected upon in interviews. The impact of this research will inform pedagogy on interdisciplinary learning, and be a persuasive argument for further Science and Design collaborations. More widely among the community, raised awareness of our immune system has the potential to modify behaviour and improve public health, as the student groups chose to focus on allergies, vaccinations and transplantation.